(untitled) (De la Crítica, 2025)
The purpose of this essay is to investigate the sources that feed the poetic imaginary of Hanni Ossott, considered one of most important feminine voices in the Venezuelan literature of the 20th century through opinions expressed by scholaris of her poetic ars. The book also gives an opinion on her poetic ideology, which led her to publish a prolific body of work, which she left as a legacy for new generations.